Analyzing the Competencies of Village Officials: A Fishbone Approach to Knowledge, Skills, Attitudes, and Leadership - Mustofa, Fariq; Utomo, Joko; Indaryani, Mamik (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: The purpose of this study is to analyze the causes and impacts of low competence among village officials from the perspective of knowledge mastery, skills, mental attitude, and leadership in Gebog District, Kudus Regency. This study also aims to identify the supporting and inhibiting factors affecting the performance and competency improvement of village officials. Furthermore, the research seeks to formulate strategic policies for improving and developing the competencies of village officials through a Fishbone analysis approach, in order to enhance the effectiveness of public services and administrative performance at the village level. Materials and methods: This study employed a qualitative descriptive research design to analyze the competence of village officials from the perspectives of knowledge mastery, skills, mental attitude, and leadership. The research was conducted in villages across Gebog District, Kudus Regency. Data were collected through in-depth interviews with key informants, including district and village government officials, village facilitators, local village assistants, and community members who utilize village administrative services. Informants were selected purposively based on their role and relevance to the research objectives. The collected data were analyzed using qualitative analysis supported by the Fishbone (cause-and-effect) diagram to identify root causes of competence-related problems, as well as supporting and inhibiting factors affecting performance improvement. Data credibility was ensured through triangulation of sources and techniques. Results: The results show that the low competence of village officials in Gebog District is influenced by both internal and external factors across the dimensions of knowledge, skills, mental attitude, and leadership. Supporting factors for competency improvement include government support, adequate budgeting, availability of technology and infrastructure, and strong leadership commitment. On the other hand, limited resources, resistance to change, insufficient development opportunities, and bureaucratic constraints hinder improvement efforts. The Fishbone analysis highlights the need for integrated strategies focusing on training and education, supervision and evaluation, incentive enhancement, bureaucratic reform, and the effective use of technology to improve overall competency. Conclusions: This study reveals that village officials' competencies are influenced by internal and external factors related to knowledge, skills, mental attitude, and leadership. Strengthening training, leadership commitment, and technological utilization are essential to improve performance, service quality, and sustainable governance effectiveness at the village level.